2016
DOI: 10.2147/ijn.s106418
|View full text |Cite
|
Sign up to set email alerts
|

The cellular uptake mechanism, intracellular transportation, and exocytosis of polyamidoamine dendrimers in multidrug-resistant breast cancer cells

Abstract: Polyamidoamine dendrimers, which can deliver drugs and genetic materials to resistant cells, are attracting increased research attention, but their transportation behavior in resistant cells remains unclear. In this paper, we performed a systematic analysis of the cellular uptake, intracellular transportation, and efflux of PAMAM-NH 2 dendrimers in multidrug-resistant breast cancer cells (MCF-7/ADR cells) using sensitive breast cancer cells (MCF-7 cells) as the control. We found that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 45 publications
4
28
0
Order By: Relevance
“…However, cytotoxicity measured as reduction of NR uptake was observed at the higher concentration of free dendrimers and D-CBZ complexes. This effect on lysosomes produced by dendrimers was previously described (Mukherjee et al, 2010;J. Zhang et al, 2016).…”
Section: In Vitro Toxicity: Cytotoxicity In N2a Cell Culturementioning
confidence: 68%
“…However, cytotoxicity measured as reduction of NR uptake was observed at the higher concentration of free dendrimers and D-CBZ complexes. This effect on lysosomes produced by dendrimers was previously described (Mukherjee et al, 2010;J. Zhang et al, 2016).…”
Section: In Vitro Toxicity: Cytotoxicity In N2a Cell Culturementioning
confidence: 68%
“…In light of the two studies mentioned earlier, it can be inferred that the present carriers may possibly be taken up by a mechanism involving nonspecific macropinocytosis, an internalization process that does not rely on the formation of the early endosome. 43 In this manner, the intracellular escape of cargo is facilitated and efficient owing to the leaky macropinosomes formed. 5 The proposed mechanism for siRNA-loaded A-L transportation across the cellular membrane and escape into cytoplasm was illustrated in Figure 12.…”
Section: Discussionmentioning
confidence: 99%
“…Although we have not studied the cellular mechanisms of synthesized conjugates penetration, the confocal microscopy images showed that all absorbed conjugates remained in endocytic and in lysosomal vesicles, with a small part of the dendrimer present in the cytoplasm of the cells (Figure 12). The influx of studied compounds also can be executed by charge-mediated adsorptive endocytosis, since each conjugate has a non-substituted free amino groups, generating positive surface charge [13,[42][43][44].…”
Section: Cellular Accumulation Of Conjugatesmentioning
confidence: 99%